A time-resolved FTIR emission study of the gas phase removal processes of CH2((X)over-tilde(3)B(1)) and CH2((a)over-tilde(1)A(1)) in collisions with O-2 - Hancock, G; Haverd, V (2003)
Time-resolved Fourier transform infrared (FTIR) emission spectroscopy has been used to study the removal of methylene in its ground (CH2(X̃3B1)) and first electronic excited state (CH2(ã1A1 ) in collisions with O2. Both the singlet and triplet removal processes yield emission from vibrationally excited CO2 and H2CO, together with a weak component from CO. The production rate of CO2 and H2CO was measured to be the same for the singlet and triplet processes and close to the rate of removal of 3CH2 by O2, and the emission intensity was essentially unchanged by quenching the singlet to the triplet in collisions with Ar. We conclude that 1CH2 is quenched to 3CH2 in collisions with O2 before reaction. © 2003 Elsevier Science B.V. All rights reserved.